Cutaneous horn, juvenile xanthogranuloma in the first decade of life: A clinico-dermatoscopic correlations - Ebtisam Elghblawi (Indian Journal of Paediatric Dermatology, 2019)
Juvenile xanthogranuloma (JXG) is a rare disorder that is present at birth, in infancy, or in adults. It can be either solitary or multiple nodules of various sizes. It can be associated with internal organ involvements, especially eyes, lung, and liver. The diagnosis can be made with confidence by clinical examination alone and confirmed by histology in doubtful cases. Hereby, I report the useful benefit of dermoscopy in evaluating and diagnosing a skin lesion that is suggestive of JXG. A 1-year-old skin type I girl presented with gradual onset of a nodular lesion on her forearm that showed a surface projecting horn. A biopsy was planned and scheduled. Clinical features were in keeping with JXG. JXG is on the spectrum of histiocyte disarrays which should be examined thoroughly in children to exclude underlying malignancy. The purpose of this article is to describe the clinical dermatoscopic correlated features of JXG. This is an interesting case of JXG presenting in a young White Swedish female child.